PERAN GURU SEBAGAI PENDIDIK DALAM PEMBENTUKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA SUKU ASLI KELAS IV SDN 6 BANTAN - Mawaddah; Dr. Elpri Darta Putra, S. Pd., M. Pd (STKIP Subang, 2026)
This study aims to describe the teacher's role as an educator in fostering discipline and responsibility among fourth-grade Indigenous students at SDN 6 Bantan. The study employs a qualitative, descriptive approach. Research informants included the school principal, the fourth-grade teacher, and fourth-grade Indigenous students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model and validated through source and technique triangulation. The results indicate that the teacher fosters discipline and responsibility through role modeling, habituation, motivation, guidance, supervision, and advice. Success in character building is supported by teacher commitment and habituation practices, while obstacles include family backgrounds, limitations in teacher supervision, and suboptimal cooperation between parents and the school. The teacher plays a significant role in shaping the students' character.